Retrospective analysis of the management of pelvic decubitus ulcers and their outcomes - Laura Damioli; Zachary Shepard; Melissa P. Wilson; Kristine M. Erlandson (Therapeutic Advances in Infectious Disease, 2023)
Background: Many patients with decubitus-related osteomyelitis are ineligible for myocutaneous flapping, and optimal management in this population is unknown. We describe treatments and outcomes of hospitalized patients with decubitus ulcer-related osteomyelitis who did not undergo surgical reconstruction or coverage. Methods: We systematically identified hospitalized patients with diagnoses of pelvic, sacral, or femoral osteomyelitis due to decubitus ulceration between 1 January 2018 and 31 December 2018. Demographics, comorbidities, laboratory data, and outcomes were collected by manual chart review. T-tests or Chi-square tests were used for descriptive statistical comparisons; logistic regressions were used to explore the odds of readmission, osteomyelitis-related readmission, and death. Results: Of 89 patients meeting inclusion criteria, 34 (38%) received surgical debridement and ⩾6 weeks of antibiotics; 55 (62%) received either antibiotics alone or debridement and <6 weeks of antibiotics. Mean age was 55 (standard deviation 18) years, 55% of patients were male, and 69% had spinal cord injury or other form of paralysis. Within 1 year, 56 (63%) patients were readmitted, 38 (44%) patients were readmitted due to complications from osteomyelitis, and 15 (17%) died. We found no significant differences in readmission (OR = 1.33, 95% CI: 0.54–3.21, p  = 0.53), readmission related to osteomyelitis (OR = 1.64, 95% CI: 0.69–4.04, p  = 0.27), subsequent sepsis (OR = 2.27, 95% CI: 0.83–6.93, p  = 0.13), or death (OR = 2.88, 95% CI: 0.83–13.4, p  = 0.12) by treatment group. Conclusions: Among patients with decubitus-related osteomyelitis who did not undergo myocutaneous flapping, outcomes were generally poor regardless of treatment, and not significantly improved with prolonged antibiotics. Prospective studies are needed to assess best practice strategies for this challenging patient population.